Effect of NPK Fertilizer Dosage and Number of Seeds On The Growth and Production of Two Cob Rice (Oryza Sativa L.) Variety of Rajasa 01 - Zeni Abdi; Sudarma Sudarma; Rolita Rolita (Syntax Corporation, 2022)
“Effect of NPK Fertilizer Dosage and Number of Seeds on Growth and Yield of Two Cob Rice (Oryza sativa L.) Rajasa 01 varieties